You are on page 1of 11

# 64 Chapter 4 The Binomial Theorem

## CHAPTER 4 11. (n − 1)! − (n − 2)! = (n − 1) × (n − 2)! − (n − 2)!

= (n − 2)!(n − 1 − 1)
Exercise 4A (p.84) = (n − 2)[(n − 2)!]
1. 3!= 3 × 2 × 1
=6 (n + 1)!
12. n +1 C3 =
3!(n + 1 − 3)!
2. 6!= 6 × 5 × 4 × 3 × 2 × 1 (n + 1)!
= 720 =
3!(n − 2)!
7! 7 × 6 × 5 × 4! (n + 1)n(n − 1)(n − 2)!
3. = =
4! 4! 3!(n − 2)!
= 7×6×5 1
= n(n + 1)(n − 1)
= 210 6
10! 10 × 9 × 8!
4. = (n + 1)!
8! 8! 13. n +1 Cn =
= 90 n!(n + 1 − n)!
(n + 1) × n!
=
5. 7! − 6! = 7 × 6! − 6! n!1!
= 6! (7 − 1) = n +1
= 6! × 6
= 6 × 6 × 5 × 4 × 3 × 2 ×1 n!
= 4 320 14. n Cn − 2 =
(n − 2)![n − (n − 2)!]
n!
6. 4! + 5! = 4! + 5 × 4! =
= 4! (1 + 5) (n − 2)! 2!
= 6 × 4 × 3 × 2 ×1 n(n − 1)(n − 2)!
=
= 144 2(n − 2)!
1
= n(n − 1)
5! 2
7. 5 C3 =
3!(5 − 3)!
5!
=
3! 2! Exercise 4B (p.90)
5 × 4 × 3!
=
3! 2! 1. ( a + b)3 = ( a)3 + 3C1 ( a)2 (b) + 3C2 ( a)(b)2 + b 3
= 10
= a 3 + 3a 2 b + 3ab 2 + b 3
6!
8. 6 C5 =
5!(6 − 5)! 2. ( x + 2 y)5
6 × 5! = ( x )5 + 5C1 ( x ) 4 (2 y) + 5C2 ( x )3 (2 y)2
=
5!1! + 5C3 ( x )2 (2 y)3 + 5C4 ( x )(2 y) 4 + (2 y)5
=6
= ( x )5 + 5( x ) 4 (2 y) + 10( x )3 (2 y)2
12! + 10( x )2 (2 y)3 + 5( x )(2 y) 4 + (2 y)5
9. 12 C9 =
9!(12 − 9)! = x 5 + 10 x 4 y + 40 x 3 y 2 + 80 x 2 y 3 + 80 xy 4 + 32 y 5
12 × 11 × 10 × 9!
=
9! 3!
= 220 3. (2 x − 3) 4
= (2 x ) 4 + 4 C1 (2 x )3 ( −3) + 4 C2 (2 x )2 ( −3)2
(n + 1)! (n + 1) × n × (n − 1) × (n − 2)!
10. = + 4 C3 (2 x )( −3)3 + ( −3) 4
(n − 2)! (n − 2)!
= n(n + 1)(n − 1) = 16 x 4 − 96 x 3 + 216 x 2 − 216 x + 81
Chapter 4 The Binomial Theorem 65

4. (3 x − 2 y)6 9. (2 x + y)10
= (3 x )6 + 6 C1 (3 x )5 ( −2 y) + 6 C2 (3 x ) 4 ( −2 y)2 The general term in the expansion
+ 6 C3 (3 x )3 ( −2 y)3 + 6 C4 (3 x )2 ( −2 y) 4 = 10 Cr (2 x )10 − r ( y)r
+ 6 C5 (3 x )( −2 y)5 + ( −2 y)6 ∴ The term in x 3 y 7 = 10 C7 (2 x )3 y 7
= 729 x 6 − 2 916 x 5 y + 4 860 x 4 y 2 − 4 320 x 3 y 3 ∴ The coefficient of x 3 y 7 = 10 C7 ⋅ 2 3 = 960
+ 2 160 x y − 576 xy + 64 y
2 4 5 6

1
10. ( − 3 x )8
1 2
5. ( x − )5 The general term in the expansion
x
1 1 1
= ( x )5 + 5C1 ( x ) 4 ( − ) + 5C2 ( x )3 ( − )2 = 8Cr ( )8 − r ( −3 x )r
x x 2
1 3 1 4 1 1
+ 5C3 ( x ) ( − ) + 5C4 ( x )( − ) + ( − )5
2
∴ The term in x 3 = 8C3 ( )5 ( −3 x )3
x x x 2
4 1 3 1 2 2 1 3
= x − 5 x ( ) + 10 x ( ) − 10 x ( )
5 1
x x x ∴ The coefficient of x 3 = 8C3 ( )5 ( −3)3
1 4 1 2
+ 5x(− ) − 5 189
x x =−
4
= x − 5 x 3 + 10 x − 10 x −1 + 5 x −3 − x −5
5

## 11. The general term in the expansion

x 2 (2 − x )6 = 6 Cr (2)6 − r ( − x )r
6. ( + )6
2 x ∴ The term in x 4 = 6 C4 (2)2 ( − x ) 4
x x 2 x 2
= ( )6 + 6 C1 ( )5 ( ) + 6 C2 ( ) 4 ( )2 ∴ The coefficient of x 4 = 6 C4 (2)2 ( −1) 4 = 60
2 2 x 2 x
x 3 2 3 x 2 2 4 The general term in the expansion
+ 6 C3 ( ) ( ) + 6 C4 ( ) ( )
2 x 2 x (2 x − 1)9 = 9 Cr (2 x )9 − r ( −1)r
x 2 5 2 6
+ 6 C5 ( )( ) + ( ) ∴ The term in x 4 = 9 C5 (2 x ) 4 ( −1)5
2 x x
x 6 x 5 2 x 2 x 2 ∴ The coefficient of x 4 = − 2 016
= ( ) + 6( ) ( ) + 15( ) 4 ( )2 + 20( )3 ( )3
2 2 x 2 x 2 x ∴ The coefficient of x 4 in the expansion of
x 2 2 4 x 2 5 2 6
+ 15( ) ( ) + 6( )( ) + ( ) (2 − x )6 − (2 x − 1)9 = 60 + 2 016 = 2 076
2 x 2 x x
1 6 3 4 15 2 60 96 64
= x + x + x + 20 + 2 + 4 + 6 12. The general term in the expansion
64 8 4 x x x
1 1
( − 6 x )6 = 6 Cr ( )6 − r ( −6 x )r
3x 3x
1
7. ( x + 2)8 = 6 Cr ( )6 − r ( −6)r x 2 r − 6
3
The general term in the expansion = 8Cr ( x )8 − r (2)r It is the constant term when 2 r − 6 = 0 , i.e r = 3 .
1
∴ The term in x 4 = 8C4 x 4 (2) 4 ∴ The constant term = 6 C3 ( )3 ( −6)3 = −160
3
∴ The coefficient of x 4 = 8C4 2 4 = 1 120
13. The general term in the expansion
1 1
8. (3 x − 2) 7 ( 4 x 2 − )9 = 9 Cr ( 4 x 2 )9 − r ( − )r
2x 2x
The general term in the expansion 1
= 9 Cr ( 4)9 − r ( − )r x18 − 3r
= 7Cr (3 x ) 7 − r ( −2)r 2
It is the constant term when 18 − 3r = 0 , i.e r = 6 .
∴ The term in x 5 = 7C2 (3 x )5 ( −2)2
1
∴ The coefficient of ∴ The constant term = 9 C6 ( 4)3 ( − )6 = 84
2
x 5 = 7C2 ⋅ 35 ( −2)2 = 20 412
66 Chapter 4 The Binomial Theorem

14. The general term in the expansion The coefficient of the third term = 4 ⋅ n C2
(1 + x ) 24
= 24 Cr x
r
4 ⋅ n C2 = 60
∴ The coefficient of x r
= 24 Cr
n!
= 15
i.e. Br = 24 Cr 2!(n − 2)!
n(n − 1) = 30
Br + 2 24 Cr + 2 57
= = n 2 − n − 30 = 0
Br 24 Cr 7
24!
(n − 6)(n + 5) = 0
( r + 2 )![ 24 − ( r + 2 )!] 57 n = 6 or −5 (rejected)
24!
=
r!( 24 − r )!
7 The general term in the expansion
(24 − r )! 57
= (1 + 2 x 2 )6 = 6 Cr (2 x 2 )r
(r + 2)(r + 1)(22 − r )! 7
(24 − r )(23 − r ) 57 ∴ The term in x 8 = 6 C4 (2 x 2 ) 4
=
(r + 2)(r + 1) 7
∴ The coefficient of x 8 = 240
57(r 2 + 3r + 2) = 7(552 − 47r + r 2 )
50 r 2 + 500 r − 3 750 = 0
18. (1 + mx 2 ) n = 1 + n C1 ( mx 2 ) + n C2 ( mx 2 )2 + L
r + 10 r − 75 = 0
2

## (r + 15)(r − 5) = 0 Comparing coefficients of x 2 and x 4 respectively,

Q r > 0 , r = −15 (rejected) m ⋅ n C1 = 14
∴ r=5 mn = 14 .............................(1)
m 2 ⋅ n C2 = 21m 2
1 n(n − 1)
15. (1 − 2 x )9 (1 + )3 m2 ⋅ = 21m 2
x 2
= [1 + 9( −2 x ) + 36( −2 x )2 + 84( −2 x )3 + L] n 2 − n − 42 = 0
1 1 1 (n + 6)(n − 7) = 0
[1 + 3( ) + 3( )2 + ( )3 ] n = 7 or −6 (rejected)
x x x
= (1 − 18 x + 144 x − 672 x 3 + L)
2 Put n = 7 into (1),
3 3 1 7m = 14
(1 + + 2 + 3 ) m=2
x x x
∴ The constant term ∴ m= 2

## = 1 + ( −18)(3) + 144(3) + ( −672) 19. The general term in the expansion

= −293
(1 + x ) n = n Cr x r
∴ The coefficient of x 4 = n C4
16. (1 − 5 x )3 (1 + 2 x )6
= [1 + 3( −5 x ) + 3( −5 x )2 + L] ∴ The coefficient of x 5 = n C5
[1 + 6(2 x ) + 15(2 x )2 + L] ∴ The coefficient of x 6 = n C6
= (1 − 15 x + 75 x + L) 2
n C4 + n C6 = 2 n C5
(1 + 12 x + 60 x 2 + L) n!
+
n!
=
2(n!)
= 1 + ( −15 + 12) x + (75 − 15 × 12 + 60) x 2 + L 4!(n − 4)! 6!(n − 6)! 5!(n − 5)!
30 (n − 4)(n − 5) 12(n − 4)
= 1 − 3 x − 45 x 2 + L + =
(n − 4)! (n − 4)! (n − 4)!
∴ a = −3 , b = −45 30 + (n − 4)(n − 5) = 12(n − 4)
n 2 − 21n + 98 = 0
17. (2 x + 1) = (1 + 2 x )
2 n 2 n
(n − 14)(n − 7) = 0
= 1 + n C1 (2 x 2 ) + n C2 (2 x 2 )2 + L n = 7 or 14
Chapter 4 The Binomial Theorem 67

20. (1 + px )(1 + qx )5 4. (3 − x + x 2 )8
= (1 + px )[1 + 5(qx ) + 10(qx )2 + L] = [3 − x (1 − x )]8
= (1 + px )(1 + 5qx + 10 q 2 x 2 + L) = 38 − 8 ⋅ 37 x (1 − x ) + 28 ⋅ 36 x 2 (1 − x )2
Comparing the coefficients of x, −56 ⋅ 35 x 3 (1 − x )3 + L
= 6 561 − 17 496 x + 17 496 x 2
5q + p = −6 ...........(1)
+20 412 x 2 (1 − 2 x + L) − 13 608 x 3 (1 + L)
Comparing the coefficients of x 2 ,
= 6 561 − 17 496 x + 37 908 x 2 − 54 432 x 3 + L
10 q + 5 pq = 0 ......(2)
2

## Put p = −6 − 5q into (2), 5. (1 − 4 x + x 2 )9

10 q 2 + 5( −6 − 5q )q = 0 = [1 − x ( 4 − x )]9
10 q 2 − 30 q − 25q 2 = 0 = 1 − 9 x ( 4 − x ) + 36 x 2 ( 4 − x )2 − L
15q 2 + 30 q = 0 = 1 − 36 x + 9 x 2 + 36 x 2 (16 + L) + L
q( q + 2 ) = 0 = 1 − 36 x + 9 x 2 + 576 x 2 + L
q = −2 or 0 (rejected)
= 1 − 36 x + 585 x 2 + L
Put q = −2 into p = −6 − 5q ,
Coefficient of x 2 = 585
p = −6 − 5( −2)
=4 6. (2 − x + x 2 )10
= [2 − x (1 − x )]10
21 − 22. No solutions are provided for the H.K.C.E.E.
questions because of the copyright reasons. = 210 − 10 ⋅ 2 9 x (1 − x ) + 45 ⋅ 2 8 x 2 (1 − x )2
− 120 ⋅ 2 7 x 3 (1 − x )3 + L
= 1 024 − 5 120 x (1 − x ) + 11 520 x 2
Exercise 4C (p.93)
(1 − 2 x + L) − 15 360 x 3 (1 + L) + L
1. (1 + x + 3 x 2 )3 = 1 024 − 5 120 x + 5 120 x 2 + 11 520 x 2
= [1 + x (1 + 3 x )] 3
− 23 040 x 3 − 15 360 x 3 + L
= 1 + 3 x (1 + 3 x ) + 3 x (1 + 3 x ) + x (1 + 3 x )
2 2 3 3
= 1 024 − 5 120 x + 16 640 x 2 − 38 400 x 3 + L
= 1 + 3 x + 9 x 2 + 3 x 2 (1 + 6 x + L) + x 3 (1 + L) Coefficient of x 3 = −38 400
= 1 + 3 x + 12 x + 19 x + L
2 3

1
2. (1 + x − 2 x 2 )6 7. (1 − + 6 x )3
3x
= [1 + x (1 − 2 x )]6 1 1
= [1 − ( − 6 x 2 )]3
= 1 + 6 x (1 − 2 x ) + 15 x 2 (1 − 2 x )2 x 3
1 1 1 1
+20 x 3 (1 − 2 x )3 + L = 1 − 3 ⋅ ( − 6 x 2 ) + 3 ⋅ 2 ( − 6 x 2 )2
x 3 x 3
= 1 + 6 x − 12 x 2 + 15 x 2 (1 − 4 x + L) 1 1
− 3 ( − 6x ) 2 3
+20 x 3 (1 + L) x 3
= 1 + 6 x + 3 x 2 − 40 x 3 + L 3 1 3 1
= 1 − ( − 6 x 2 ) + 2 ( − 4 x 2 + 36 x 4 ) + L
x 3 x 9
3. (1 − x − x 2 )5 Constant term = 1 + 3( −4) = −11
= [1 − x (1 + x )] 5

= 1 − 5 x (1 + x ) + 10 x 2 (1 + x )2 8. (1 − x + 2 x 2 ) n
−10 x (1 + x ) + L
3 3
= [1 − x (1 − 2 x )]n
= 1 − 5 x − 5 x 2 + 10 x 2 (1 + 2 x + L) = 1 − n C1 x (1 − 2 x ) + n C2 x 2 (1 − 2 x )2 + L
−10 x (1 + L)
3
= 1 − n C1 x (1 − 2 x ) + n C2 x 2 (1 − 4 x + 4 x 2 ) + L
= 1 − 5 x + 5 x 2 + 10 x 3 + L
= 1 − n C1 x + (2 n C1 + n C2 ) x 2 + L
68 Chapter 4 The Binomial Theorem

2 n C1 + n C2 = 44 n(n − 1) 4
= 1 + nx 2 + nx 3 + x (1 + 2 x
1 2
2 n + n(n − 1) = 44 n(n − 1)(n − 2) 6
2 +x2 ) + x (1 + 3 x
6
n 2 + 3n − 88 = 0 + L) + L
(n − 8)(n + 11) = 0 n(n − 1) 4
n = 8 or −11 (rejected) = 1 + nx 2 + nx 3 + x
2
n(n − 1) 6
+ n(n − 1) x 5 + x
9. (a) (1 − x + 2 x 2 )6 2
n(n − 1)(n − 2) 6
= [1 − x (1 − 2 x )]6 + x
6
= 1 − 6 x (1 − 2 x ) + 15 x 2 (1 − 2 x )2 n(n − 1)(n − 2) 7
+ x +L
− 20 x 3 (1 − 2 x )3 + L 2
= 1 − 6 x + 12 x 2 + 15 x 2 (1 − 4 x + L) Coefficient of x = n(n − 1)
5

− 20 x 3 (1 + L) 1
Coefficient of x 7 = n(n − 1)(n − 2)
= 1 − 6 x + 27 x 2 − 80 3 + L 2
(b) (1 − x + 2 x 2 )6 (1 + x )6 Coefficient of x 7
(b) =5
= (1 − 6 x + 27 x 2 − 80 3 x 3 + L) Coefficient of x 5
1 n( n − 1)( n − 2 )
(1 + 6 x + 15 x 2 + 20 x 3 + L) 2 =5
n(n − 1)
= 1 + x (27 − 6 × 6 + 15)
2
n−2
+ x 3 ( −80 + 27 × 6 − 6 × 15 + 20) + L =5
2
= 1 + 6 x 2 + 12 x 3 + L n = 12
a = 0 , b = 6 , c = 12
12. (1 + px + qx 2 ) 4
10. (a) (1 + x − 2 ax 2 ) n = [1 + x ( p + qx )]4
= [1 + x (1 − 2 ax )]n = 1 + 4 x ( p + qx ) + 6 x 2 ( p + qx )2
= 1 + n C1 x (1 − 2 ax ) + 4 x 3 ( p + qx )3 + L
+ n C2 x 2 (1 − 2 ax )2 + L = 1 + 4 px + 4 qx 2 + 6 x 2 ( p 2 + 2 pqx + L)
= 1 + nx (1 − 2 ax ) + 4 x 3 ( p3 + L) + L
1
+ n(n − 1) x 2 (1 + L) + L = 1 + 4 px + 4 qx 2 + 6 p 2 x 2 + 12 pqx 3
2
n(n − 1) 2 + 4 p3 x 3 + L
= 1 + nx − [2 an − ]x + L
2 = 1 + 4 px + 2(3 p 2 + 2 q ) x 2
(b) Coefficient of x = n = 7 + 4 p( p 2 + 3q ) x 3 + L

## Comparing the coefficients of x 2 , 2(3 p 2 + 2 q ) = 0 ..............(1)

n(n − 1) 4 p( p 2 + 3q ) = −112 ......(2)
−[2 an − ]= 0
2 By (1), 2 q = −3 p 2
7×6
2 a(7) − =0 3
2 q = − p2
3 2
a= −3 2
2 Substitute into (2), 4 p[ p 2 + ( p )(3)] = −112
2
7
11. (a) (1 + x 2 + x 3 ) n 4 p( − p 2 ) = −112
2
= [1 + x 2 (1 + x )]n −14 p3 = −112
n(n − 1) 4 p3 = 8
= 1 + nx 2 (1 + x ) + x (1 + x )2
2 p=2
n(n − 1)(n − 2) 6
+ x (1 + x )3 + L ∴
3
q = − ( 4) = −6
6 2
Chapter 4 The Binomial Theorem 69

13. (a) (1 − tx − x 2 ) 7 4. (1 + 2 x )3 (1 − x )2
= [1 − x (t + x )]7 = [1 + 3(2 x ) + 3(2 x )2 + (2 x )3 ](1 − 2 x + x 2 )
= 1 − 7 x (t + x ) + 21x (t + x )
2 2
= (1 + 6 x + 12 x 2 + 8 x 3 )(1 − 2 x + x 2 )
− 35 x 3 (t + x )3 + L = 1 + ( −2 + 6) x + (1 − 12 + 12) x 2 + (8 − 24 + 6) x 3
= 1 − 7tx − 7 x 2 + 21x 2 (t 2 + 2tx + L) + (12 − 16) x 4 + 8 x 5
− 35 x 3 (t 3 + L) + L = 1 + 4 x + x 2 − 10 x 3 − 4 x 4 + 8 x 5
= 1 − 7tx − 7 x 2 + 21t 2 x 2 + 42tx 3
− 35t 3 x 3 + L 1
5. (2 x − )12
= 1 − 7tx + 7(3t − 1) x
2 2 x
The general term is
12 − r
−7t (5t 2 − 6) x 3 + L 12 Cr (2 x ) ( − x −1 )r = 12 Cr (2)12 − r ( −1)r x12 − 2 r
(b) By (a), comparing the coefficients of x 3 , It is the constant term when 12 − 2 r = 0 . ∴ r = 6
−91t = −7t (5t − 6)
2 2 ∴ The constant term = 12 C6 ⋅ 2 6 ( −1)6 = 59 136
13t = 5t 2 − 6
5t 2 − 13t − 6 = 0 x2 2 8
6. ( − )
(5t + 2)(t − 3) = 0 2 x
2 The general term is
t = 3, − (rejected)
5 x2 8− r 2 r
8 Cr () ( − ) = 8Cr ( −1)r 2 2 r − 8 x16 − 3r
Coefficient of x 2 = 7(27 − 1) 2 x
= 182 Term in x 4 when 16 − 3r = 4 , ∴ r = 4
Coefficient of x 4 = 8 C4 ( −1) 4 2 8 − 8 = 70
14 − 15. No solutions are provided for the H.K.C.E.E.
questions because of the copyright reasons. 7. (1 + x )16 = 1 + 16 C1 x + 16 C2 x 2 + L
Coefficient of the 3rd term = 16 C2 = 120
Revision Exercise 4 (p.95)
8. (2 − x )15
1
1. (2 x − )5 = 215 − 15C1 214 x + L + 15C12 2 3 ( − x )12 + L
x
1 1
= (2 x )5 − 5(2 x ) 4 ( ) + 10(2 x )3 ( )2 Coefficient of the 13th term = 15 C12 2 3 = 3 640
x x
2 1 3 1 4
−10(2 x ) ( ) + 5(2 x )( ) − ( )5
1 9. (2 + x + x 3 ) 7
x x x = [2 + x (1 + x 2 )]7
= 32 x 5 − 80 x 3 + 80 x − 40 x −1+ 10 x −3 − x −5
= 2 7 + 7 C1 ⋅ 2 6 x (1 + x 2 ) + 7C2 ⋅ 2 5 x 2
(1 + x 2 )2 + 7C3 ⋅ 2 4 x 3 (1 + x 2 )3 + L
2. ( a − b)3 ( a + b)3 = 128 + 448 x (1 + x 2 ) + 672 x 2 (1 + L)
= ( a 2 − b 2 )3 + 560 x 3 (1 + L) + L
= a 6 − 3a 4 b 2 + 3a 2 b 4 − b 6 = 128 + 448 x + 672 x 2 + 1 008 x 3 + L

10. (3 + 2 x − x 2 ) 4
1 = [3 + x (2 − x )]4
3. ( x 2 − ) 4
x
1 1 = 34 + 4 ⋅ 33 x (2 − x ) + 6 ⋅ 32 x 2 (2 − x )2
= x 8 − 4( x 2 )3 ( ) + 6( x 2 )2 ( )2 + 4 ⋅ 3 x 3 ( 2 − x )3 + L
x x
2 1 3
− 4( x )( ) + ( − )
1 4 = 81 + 108 x (2 − x ) + 54 x 2 ( 4 − 4 x + L)
x x + 12 x 3 (8 − L) + L
= x − 4 x + 6 x − 4 x −1 + x −4
8 5 2
= 81 + 216 x + 108 x 2 − 120 x 3 + L
70 Chapter 4 The Binomial Theorem

## It is the constant term when

11. (1 + 2 x ) 4 (1 − x )6
2 n − 18 = 0 . ∴ n = 9
= (1 + 8 x + 24 x 2 + 32 x 3 + L)
∴ The value of the 7th term
(1 − 6 x + 15 x 2 − 20 x 3 + L)
21
= 1 + 2 x − 9 x 2 − 12 x 3 + L = 9 C6 ⋅ 2 −3 =
2

## 12. (1 − 2 x ) 4 (1 + x ) 7 17. The general term in the expansion

= (1 − 8 x + 24 x 2 + L)(1 + 7 x + 21x 2 + L) a a
( x 2 + ) 7 = 7Cr ( x 2 ) 7 − r ( )r
2x 2x
Coefficient of x 2 = 21 − 56 + 24 = −11 a
= 7Cr ( )r x14 − 3r
2
1
13. (1 − + 4 x 2 )4 a 21 2
2x ∴ A8 = 7C2 ( )2 = a
1 2 4
= [1 − (1 − 8 x 3 )]4 a 7
2x A11 = 7C1 ( ) = a
1 1 2 2
= 1 − 4( )(1 − 8 x 3 ) + 6( )2 (1 − 8 x 3 )2 A8 = 6 A11
2x 2x
21 2 7
1 3 1
− 4( ) (1 − 8 x ) + ( ) 4 (1 − 8 x 3 ) 4
3 3 a = 6( )a
2x 2x 4 2
a( a − 4 ) = 0
Constant term = 1 + 12 = 13 a = 4 or 0 (rejected)

14. (1 + x − 2 x 2 )9 (1 + x ) 4 2 n 2
18. ( ax + ) = ( ax ) n + n( ax ) n −1 ( 2 )
= [1 + x (1 − 2 x )]9 (1 + x ) 4 x2 x
= [1 + 9 x (1 − 2 x ) + 36 x 2 (1 − 2 x )2 + 84 x 3 (1 − 2 x )3 n(n − 1) 2
+ ( ax ) n − 2 ( 2 )2 + L
+ L](1 + 4 x + 6 x 2 + 4 x 3 + L) 2 x
= [1 + 9 x − 18 x 2 + 36 x 2 (1 − 4 x + L) n(n − 1) 4
The third term = ( ax ) n − 2 ( 4 )
+ 84 x 3 (1 + L) + L](1 + 4 x + 6 x 2 + 4 x 3 + L) 2 x
= 2 n(n − 1)a n − 2 x n − 6
= (1 + 9 x + 18 x 2 − 60 x 3 )(1 + 4 x + 6 x 2 + 4 x 3 + L)
Q The third term is independent of x.
Coefficient of x 3 = 4 + 9 × 6 + 18 × 4 − 60 = 70
∴ n − 6 = 0 , i.e. n = 6
1 The coefficient of the third term:
15. (1 + 2 x ) n = 1 + 2 nx + n(n − 1)(2 x )2
2 15
1 2 n(n − 1)a n − 2 =
+ n(n − 1)(n − 2)(2 x )3 4
6 4 15
1 2(6)(5)a =
+ n(n − 1)(n − 2)(n − 3)(2 x ) 4 + L 4
24 1
a =
4
Q Coefficient of x 3 = Coefficient of x 4 16
1 1
2 3 ⋅ n(n − 1)(n − 2) 2 4 ⋅ n(n − 1)(n − 2)(n − 3) a = − or (rejected)
∴ = 2 2
6 24
4 2
= (n − 3) 19. (1 + 2 x )5 (1 − x ) n
3 3
2 = n−3 = [1 + 5(2 x ) + 10(2 x )2 + L]
n=5 n(n − 1) 2
[1 − nx + x + L]
2
16. The general term in the expansion
= (1 + 10 x + 40 x 2 + L)
1 1
(2 x 2 + ) n = n Cr (2 x 2 ) n − r ( )r n2 − n 2
2x 2x (1 − nx + x + L)
2
= n Cr ⋅ 2 x n − 2 r x 2 n − 3r
(a) Coefficient of x = − n + 10 = 1
∴ The 7th term = n C6 ⋅ 2 n −12 x 2 n −18 n =9
Chapter 4 The Binomial Theorem 71

n2 − n q = 6 ...............................(1)
(b) Coefficient of x 2 = − 10 n + 40 (b)  1
 2 q(2 p + q − 1) = 27 .......(2)
2
92 − 9
= − 90 + 40 Substitute q = 6 into (2).
2
= −14 1
(6)(2 p + 6 − 1) = 27
2
2p + 5 = 9
20 − 22. No solutions are provided for the H.K.C.E.E. p=2
questions because of the copyright reasons.
1
Coefficient of x 3 = (6)(5)(12 + 6 − 2)
x x n(n − 1) x 2 6
23. (1 + ) n = 1 + n( ) + ( ) = (5)(16)
2n 2n 2 2n
1 x 3 = 80
+ n(n − 1)(n − 2)( ) L
6 2n 25. (a) (1 − px )6 − (1 + x ) n
Coefficient of x 2 = n(n − 1) ( 1 )2 =
1
= (1 − 6 px + 15 p 2 x 2 + L)
2 2n 10 1
n −1 1 − [1 + nx + n(n − 1) x 2 + L]
= 2
8n 10 1
2n = 10 = ( −6 p − n) x + [15 p 2 − n(n − 1)]x 2 + L
2
n =5 1
= −(6 p + n) x + (30 p − n 2 + n) x 2 + L
2
1 1 2
Coefficient of x 3 = n(n − 1)(n − 2)( )3
6 2n (b) −(6 p + n) = −17 .................(1)
1 1 3
= ×5× 4×3×( ) 1
6 10 (30 p 2 − n 2 + n) = 50 .......(2)
1 2
=
100 17 − n
By (1), p = ..............(3)
6
Put (3) into (2),
24. (a) (1 + x + px 2 ) q
1 17 − n 2
= [1 + x (1 + px )]q [30( ) − n 2 + n] = 50
2 6
1
= 1 + qx (1 + px ) + q(q − 1) x 2 (1 + px )2 5(289 − 34n + n 2 ) − 6n 2 + 6n = 600
2
1 n 2 + 164n − 845 = 0
+ q(q − 1)(q − 2) x 3 (1 + px )3 + L
6 n=5 or −169 (rejected)
1
= 1 + qx + pqx 2 + q(q − 1) x 2 (1 + 2 px Put n = 5 into (3),
2
1
+ L) + q(q − 1)(q − 2) x 3 (1 + L) + L 17 − 5
6 p= =2
6
q(q − 1) 2
= 1 + qx + pqx 2 + x
2
q(q − 1)(q − 2) 3 Enrichment 4 (p.97)
+ pq(q − 1) x 3 + x +L
6 b
q(q − 1) 2 1. (a) ( ax + ) n
= 1 + qx + [ pq + ]x x
2 b b
q(q − 1)(q − 2) 3 = ( ax ) n + n C1 ( ax ) n −1 ( ) + n C2 ( ax ) n − 2 ( )2
+[ pq(q − 1) + ]x + L x x
6
n −3 b 3 n−4 b 4
1 + n C3 ( ax ) ( ) + n C4 ( ax ) ( ) +L
= 1 + qx + q(2 p + q − 1) x 2 x x
2
= a n x n + n C1a n −1bx n − 2 + n C2 a n − 2 b 2 x n − 4
1
+ q(q − 1)(6 p + q − 2) x 3 + L
6 + n C3 a n − 3b 3 x n − 6 + n C4 a n − 4 b 4 x n − 8 + L
72 Chapter 4 The Binomial Theorem

(b) The fifth term is the constant term. n(n − 1)(n − 2) 7n(n − 1)
n−8 = 0 b= + + 7n − 49
6 2
n=8 (3)(2) 7(3)(2)
= + + 7(3) − 49
6 2
2. (a) (1 + 3 x ) m + (1 + 5 x ) n = −6
m( m − 1)
= [1 + m(3 x ) + (3 x )2 + L] + 4. Let the three consecutive coefficients be the
2
n(n − 1) coefficients of the (r − 1) th, rth and (r + 1) th
[1 + n(5 x ) + (5 x )2 + L] terms, then
2
= 2 + (3m + 5n) x n Cr − 2 = 3a ................................(1)
9m( m − 1) 25n(n − 1) 2 = 12 a ..............................(2)
+[ + ]x + L n Cr −1
2 2
n Cr = 28a .............................. (3)
Comparing coefficients of x,
3m + 5n = 19 (1) n Cr − 23a
=
,
Q m and n are positive integers. (2) n Cr −1 12 a
r −1 3
∴ m = 3, n = 2 =
n − r + 2 12
9m( m − 1) 25n(n − 1) 15r − 3n = 18 ..................(4)
(b) a = +
2 2 (2) n Cr −112 a
9(3)(2) 25(2) , =
= + (3) C
n r 28a
2 2 r 3
= 52 =
n − r +1 7
10 r − 3n = 3 .....................(5)
3. (a) (1 + x − 2 x 2 ) 7 (4) − (5) : 5r = 15
= [1 + x (1 − 2 x )] 7
r=3
= 1 + 7 x (1 − 2 x ) + 21x 2 (1 − 2 x )2 Put r = 3 into (4),
+ 35 x 3 (1 − 2 x )3 + L 15(3) − 3n = 18
= 1 + 7 x − 14 x + 21x (1 − 4 x + L)
2 2 n=9
+ 35 x 3 (1 + L) + L Put n = 9 and r = 3 into (3),
= 1 + 7 x + 7 x − 49 x + L
2 3
9 C3 = 28a
a=3
(b) (1 + x − 2 x ) (1 + x )
2 7 n

= (1 + 7 x + 7 x 2 − 49 x 3 + L)[1 + nx +
n(n − 1) 2 n(n − 1)(n − 2) 3 Classwork 1 (p.84)
x + x + L]
2 6
n(n − 1) 1. (a) 5!= 5 × 4 × 3 × 2 × 1
= 1 + ( 7 + n) x + [ + 7n + 7]x 2 = 120
2
n(n − 1)(n − 2) 7n(n − 1)
+[ + + 7n − 49]x 3 9! 9 × 8 × 7!
6 2 (b) =
+L 7! 7!
= 72
By comparing coefficients,
7 + n = 10 (c) =
7!
7 C3
n=3 3!(7 − 3)!
7!
n(n − 1) =
a= + 7n + 7 3! 4!
2 7 × 6 × 5 × 4!
(3)(2) =
= + 7(3) + 7 3! 4!
2 = 35
= 31
Chapter 4 The Binomial Theorem 73

## n! ∴ The coefficient of x 3 = 7C3 ( −2)3

2. (a) n C3 =
3!(n − 3)! = −280
n(n − 1)(n − 2)n − 3!
= (b) The general term in the expansion
6(n − 3)!
1 = 6 Cr ( x 2 )6 − r (2)r
= n(n − 1)(n − 2)
6 ∴ The term in x 6 = 6 C3 ( x 2 )3 (2)3

## n! ∴ The coefficient of x 6 = 160

(b) n Cn − 3 =
(n − 3)![n − (n − 3)]! (c) The general term in the expansion
1
= 6 Cr (3 x )6 − r ( )r
n!
=
(n − 3)! 3! x
n(n − 1)(n − 2)(n − 3)! = 6 Cr ⋅ 36 − r x 6 − 2 r
=
(n − 3)! 3! It is the constant term when
1
= n(n − 1)(n − 2) 6 − 2r = 0 . ∴ r = 3
6
∴ The constant term = 6 C3 ⋅ 33 = 540
(n + 2)! (d) The general term in the expansion
(c) n + 2 C2 =
2!(n + 2 − 2)! 2
(n + 2)! = 9 Cr ( x 2 )9 − r ( − )r
= x
2! n! 18 − 2 r 2
(n + 2)(n + 1)n! = 9 Cr ( x )( − )r
= x
2! n! = 9 Cr ( −2)r x18 − 3r
1
= (n + 1)(n + 2)
2 It is the constant term when
18 − 3r = 0 . ∴ r = 6
Classwork 2 (p.89) ∴ The constant term = 9 C6 ( −2)6 = 5 376

1. (a) (1 + 2 a) 4
= 1+ Classwork 3 (p.90)
4 C1 (2 a) + 4 C2 (2 a)
2

+ 4 C3 (2 a) + (2 a)
3 4
1. (a) ( x 2 − 1)9
= 1 + 8a + 24 a + 32 a + 16 a
2 3 4
= ( −1 + x 2 )9
(b) (3 − b) 4 = ( −1)9 + 9( −1)8 ( x 2 ) + 36( −1) 7 ( x 2 )2 + L
= (3) 4 + = −1 + 9 x 2 − 36 x 4 + L
4 C1 (3) ( − b ) + 4 C2 (3) ( − b )
3 2 2

+ 1
4 C3 (3)( − b ) + ( − b)
3 4
(b) (2 + ) 4
x
= 81 − 108b + 54b − 12 b + b
2 3 4
1 1
= (2) 4 + 4(2)3 ( ) + 6(2)2 ( )2
(c) ( x + 2 y) 3 x x
1 3 1 4
= ( x )3 + 3C1 ( x )2 (2 y) + 3C2 ( x )(2 y)2 + (2 y)3 + 4(2)( ) + ( )
x x
= x 3 + 6 x 2 y + 12 xy 2 + 8 y 3 32 24 8 1
= 16 + + + +
x x2 x3 x 4
(d) ( y − 3 x )3 = ( y)3 + 3C1 ( y)2 ( −3 x ) 1
(c) ( x 2 − 1)9 (2 + ) 4
+ 3C2 ( y)( −3 x )2 + ( −3 x )3 x
= y 3 − 9 y 2 x + 27 yx 2 − 27 x 3 = ( −1 + 9 x 2 − 36 x 4 + L)
32 24 8 1
2. (a) The general term in the expansion (16 + + 2 + 3 + 4)
x x x x
= 7Cr ( −2 x )r ∴ The constant term in the expansion
∴ The term in x 3 = 7C3 ( −2 x )3 = ( −1)(16) + 9(24) + ( −36)(1)
= 164
74 Chapter 4 The Binomial Theorem

## ∴ Comparing the coefficients of x,

2. (3 x 2 + 1) n = (1 + 3 x 2 ) n
n C1 p = −7
= 1 + n C1 (3 x 2 ) + n C2 (3 x 2 )2
np = −7
+ n C3 (3 x 2 )3 + L −7
p= ......................(1)
Compare coefficient to a + bx 2 + cx 4 + dx 6 + L n
b = 3 ⋅ n C1 , d = 27 ⋅ n C3 Comparing the coefficients of x 2 ,
Q d = 108b 2 ⋅ n C1 + p 2 ⋅ n C2 = 35
1
27 ⋅ n C3 = 108(3 ⋅ n C1 ) 2 n + p 2 ⋅ n(n − 1) = 35 ..........(2)
n! n! 2
27 ⋅ = 324 ⋅ Put (1) into (2),
3!(n − 3)! (n − 1)!
9 −7 2 1
(n − 1)(n − 2) = 324 2n + ( ) n(n − 1) = 35
2 n 2
n 2 − 3n + 2 = 72 49 n − 1
2n + ⋅ = 35
n 2 − 3n − 70 = 0 2 n
(n + 7)(n − 10) = 0 4n 2 + 49n − 49 = 70 n
n = 10 or −7 (rejected) 4n 2 − 21n − 49 = 0
(n − 7)( 4n + 7) = 0
7
n=7 or − (rejected)
Classwork 4 (p.92) 4
7
1. (1 + x − 3 x 2 )6 Put n = 7 into (1), p = − = −1
7
= [1 + x (1 − 3 x )]6
= 1 + 6 x (1 − 3 x ) + 15 x 2 (1 − 3 x )2
+ 20 x 3 (1 − 3 x )3 + L
= 1 + 6 x − 18 x 2 + 15 x 2 (1 − 6 x + L)
+ 20 x 3 (1 + L) + L
= 1 + 6 x − 18 x 2 + 15 x 2 − 90 x 3 + 20 x 3 + L
= 1 + 6 x − 3 x 2 − 70 x 3 + L
1
2. (1 + x − 3 x 2 )6 (1 − )3
x
= (1 + 6 x − 3 x 2 − 70 x 3 + L)
1 1 1
[1 + 3( − ) + 3( − )2 + ( − )3 ]
x x x
= (1 + 6 x − 3 x 2 − 70 x 3 + L)
3 3 1
(1 − + 2 − 3 )
x x x
∴ The constant term = 1 + 6( −3) − 3(3) − 70( −1)
= 44

Classwork 5 (p.93)
(1 + px + 2 x 2 ) n
= [1 + x ( p + 2 x )]n
= 1 + n C1 x ( p + 2 x ) + n C2 x 2 ( p + 2 x )2 + L
= 1 + n C1 px + 2 n C1 x 2 + n C2 x 2 ( p 2 + L) + L
= 1 + n C1 px + (2 ⋅ n C1 + p 2 ⋅ n C2 ) x 2 + L